(untitled) (International Journal of Engineering and Computer Science, 2015)
Steganography differs from cryptography in the sense that where cryptography focuses on keeping the contents of a message secret, steganography focuses on keeping the existence of a message secret. Various techniques of image Steganography are explained such as spatial domain technique, Spread Spectrum Technique, Transform Domain Technique, Statistical Technique, distortion technique. In this paper various Image Steganography techniques are reviewed.